Numerical simulation of stress distribution of a Femur-Menisci-Tibia bone during normal standing, normal walking, and standing with a cane - A. Prommarat (2018)
© 2014 IEEE. This paper proposes a mathematical model of stress distribution of a Femur-Menisci-Tibia (F-M-T) bone in three-dimensional spaces of a person with 90kg body weight during normal standing, normal walking, and standing with a cane. Numerical simulation based on the finite element (FE) method is carried out. Our results suggest that the Von Mises stress of menisci during standing with a cane is lowest while the stress during normal standing is highest among three activities. Our study highlights that a cane can reduce the Von Mises stress and help prevent bone damage in a patient.